New traveling wave solutions of the higher dimensional nonlinear partial differential equation by the exp-function method - Naher, Hasibun; Abdullah, Farah Aini; Akbar, M. Ali (© 2012 Journal of Applied Mathematics, 2016)
This article was published in the Journal of Applied Mathematics [© 2012 Hasibun Naher et al.] and the definite version is available at :http://dx.doi.org/10.1155/2012/575387 The Journal's website is at:https://www.hindawi.com/journals/jam/2012/575387/